FACTORS AFFECTING THE CHOICE OF ADAPTATION STRATEGIES TO CLIMATE EXTREMES: THE CASE OF SMALLHOLDER FARMERS IN SOUTHERN ZAMBIA - Kiru Sichoongwe; Jinxia Wang (Socio-Economics/Agribusiness Department, 2023)
This study assesses smallholder farmers' adaptation to climate extremes and its contributing factors in Zambia's southern province. The study employed primary data from 270 smallholder farmers, constituting the sample size.Â According to the study's findings, change crop variety was adopted by 43% of the farmers. Other strategies of adaptation that were employed include; agricultural insurance, change sow/harvest date, crop diversification and soil conservation. The findings also showed that the various adaptation strategies (agricultural insurance, change sow/harvest date, crop diversification and soil conservation), correlated positively with age, education, distance, farming experience, radio ownership, an ox, a plough, and extension source. The study makes the following recommendations; (a) enhancing the education and awareness level of farmers towards climate extreme, (b) when drafting policy, asset formation should be considered, and (c) when developing and implementing adaptation strategies, indigenous knowledge should be taken into account.